2012
DOI: 10.1111/bjh.12034
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance angiography‐defined intracranial vasculopathy is associated with silent cerebral infarcts and glucose‐6‐phosphate dehydrogenase mutation in children with sickle cell anaemia

Abstract: Summary Silent cerebral infarct (SCI) is the most commonly recognized cause of neurological injury in sickle cell anaemia (SCA). We tested the hypothesis that magnetic resonance angiography (MRA)-defined vasculopathy is associated with SCI. Furthermore, we examined genetic variations in glucose-6-phosphate dehydrogenase (G6PD) and HBA (α-globin) genes to determine their association with intracranial vasculopathy in children with SCA. Magnetic resonance imaging (MRI) of the brain and MRA of the cerebral vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 52 publications
1
57
3
Order By: Relevance
“…11,2629 The borderzone, also referred to as the “watershed region”, consists of the area supplied by the terminal collaterals of two adjacent large vessels, such as the anterior cerebral artery and middle cerebral artery. The borderzone is suspected to have lower cerebral blood flow (CBF) relative to other areas of the brain and be uniquely sensitive to states of hypoperfusion, such as in adults with ipsilateral internal carotid artery occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…11,2629 The borderzone, also referred to as the “watershed region”, consists of the area supplied by the terminal collaterals of two adjacent large vessels, such as the anterior cerebral artery and middle cerebral artery. The borderzone is suspected to have lower cerebral blood flow (CBF) relative to other areas of the brain and be uniquely sensitive to states of hypoperfusion, such as in adults with ipsilateral internal carotid artery occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…579 The SIT Trial found that 2 variations in the G6PD gene that are linked to reduced enzymatic function, rs1050828 and rs1050829, were associated with vasculopathy in male participants with SCD (OR, 2.78; 95% CI, 1.04–7.42; P =0.04). 580 Further validation of these findings is required before these genetic variations can be used for stroke risk prediction.…”
Section: Well-documented and Modifiable Risk Factorsmentioning
confidence: 99%
“…Some studies indicate no association between G6PD deficiency and stroke or cerebral vasculopathy, 17,23,24 while others do show an increased frequency of magnetic resonance index (MRI)- or transcranial Doppler (TCD)-defined cerebral vasculopathy. 18,25,26 These conflicting data limit the prognostic utility of G6PD deficiency.…”
Section: Determinants Modifiers and Correlates Of Disease Severitymentioning
confidence: 99%